MINAT BERWIRAUSAHA MAHASISWA STMIK STIKOM INDONESIA - Mariani, Wayan Eny (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2019)
Colleges have the opportunity to foster an entrepreneurial spirit in the younger generation before they begin to enter the real world of work. STMIK STIKOM Indonesia is an information technology-based colleges that encourage students to become entrepreneurs. To be able to find out the effectiveness of conducting entrepreneurship education and the interest of STMIK STIKOM Indonesia students in entrepreneurship, a study was conducted on the influence of entrepreneurial personality, entrepreneurial knowledge, and the environment on the interests of STMIK STIKOM Indonesia student entrepreneurship. This research is a quantitative research that uses survey methods. The population of this study was STMIK STIKOM Indonesia students. The technique of data collection is done by questionnaires and the determination of samples using simple random sampling method. Data analysis was performed using multiple linear regression analysis. The results of data analysis show that entrepreneurial personality, entrepreneurial knowledge and the environment have a significant influence on the interest in entrepreneurship in STMIK STIKOM Indonesia students.